Air breakdown characteristics in plane-plane and sphere gap electrode configuration under lightning impulse - Rosdi, Hairierosniza (2014)
This report describes the air breakdown characteristics in plane-plane and sphere gap electrode configuration under lightning impulse. The breakdown in air (spark breakdown) is the transition of a non-sustaining discharge into a selfsustaining discharge. In electrical power system, high voltage power equipments are mainly subjected with spark over voltage. This over voltage which may causes by the lightning strokes, switching action and so on. In this project, two different electrodes (plane-plane and sphere gap) are used to study the air breakdown characteristics. This two electrodes are tested by using different gap start with 0.5 cm, 1.0 cm until 2.5 cm. Refer to British Standard BS EN 60060 that explained detail about the general definitions and test requirements for high voltage test techniques to construct in this project. In addition, TERCO lightning impulse circuit are use to obtain the lightning impulse waveform. To estimate U50 during the experimental, up and down method are used with the value of n ≥ 20. Finite element method magnetic software (FEMM) is use to shows the potential higher electric field occurs around the electrodes. Vector and contour around the electrodes also can be viewed. From this project can conclude that electric field distribution between two conductors (or electrodes) depends on applied voltage (U50), gap between electrodes, types and surface of electrodes. In the end of this project, the relationship between voltage (U50) and gap, electric field (|Emax|) and gap, field utilization factor (η) and gap, U50 and field utilization factor (η) and electric field (|Emax|) and field utilization factor (η) have been constructed with help of graph.